V-021 REPORT OF AN ACQUIRED INTERCOSTAL HERNIA REPAIR USING A BILAYER MESH. (13th October 2022) - Burns, E; Aliar, A; Baltatzis, M; O'keeffe, N; Sheen, A J
Abstract: Aim: A 53-year-old male underwent a T10/11 discectomy with partial removal of the right T9 rib. 10 years later, he developed an acquired painful intercostal hernia, worsened by leaning against the defect. CT imaging demonstrated an 8cm hernial defect containing the posterior lobe (segment VII) of the liver with a loss of integrity of the diaphragm. Methods: Open surgical repair though the original incision was undertaken, with the patient in the left lateral position. The hernia was entirely reducible in this position. Results: The liver was replaced into the peritoneal cavity, the hernial sac and the weakness at the postero-lateral edge of the diaphragm were then identified. The edges of the hernial sac were dissected off the ribs. An intraperitoneal mesh (SymbotexTM; Medtronic, Lyon) was cut to size, placed, and fixed to the undersurface of the ribs, with a 5cm overlap obtained medially and laterally. Care was taken to avoid damaging the neurovascular bundle and breach of the pleural cavity was not observed. A bridging mesh was then used to reinforce the repair (VersatexTM; Medtronic, Lyon) with fixation to the ribs using ethibond sutures and cyanoacrylate glue (Glubran®; Viareggio). The repair was checked by Valsalva manoeuver prior to wound closure. Post operative pain control was achieved using intercostal nerve block and patient-controlled analgesia. A post-operative chest x-ray did not demonstrate a pneumothorax. The patient was discharged on postoperative day 2. Discussion: The patient experienced no serious postoperative sequelae and was pain free with no hernia at 30 days post-surgery.